Identifikasi Senyawa Antioksidan Dalam Spons Callyspongia SP Dari Kepulauan Seribu - Hanani, Endang (Majalah Ilmu Kefarmasian, 2005)
Antioxidant activity and identification of antioxidative compounds of Callyspongia sponge from Seribu Island (Kepulauan Seribu) were investigated. The sponge was extracted with acetone and the extract was concentrated using rotary vacuum evaporator. DPPH and tiocyanate methods were used to examine the antioxidant activity of the extract. The extract exhibited strong antioxidant activity in DPPH method with IC50 of 41.21 Âµg/ml. Chemical analysis indicated that the antioxidative compound in the sponge was alkaloid group.